2023
DOI: 10.3390/ijms24054328
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Discovery of Anticancer Peptides through Deep Forest Architecture with Deep Graphical Representation

Abstract: Cancer is one of the leading diseases threatening human life and health worldwide. Peptide-based therapies have attracted much attention in recent years. Therefore, the precise prediction of anticancer peptides (ACPs) is crucial for discovering and designing novel cancer treatments. In this study, we proposed a novel machine learning framework (GRDF) that incorporates deep graphical representation and deep forest architecture for identifying ACPs. Specifically, GRDF extracts graphical features based on the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Previous studies have demonstrated that incorporating such evolutionary information can enhance the performance of protein function prediction tasks (An et al, 2019; Li & Liu, 2020). Finally, the Zsl matrix of amino acids provides rich information on physicochemical properties, which is crucial for building robust models in multi‐omics tasks (Lin et al, 2021; Yao et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that incorporating such evolutionary information can enhance the performance of protein function prediction tasks (An et al, 2019; Li & Liu, 2020). Finally, the Zsl matrix of amino acids provides rich information on physicochemical properties, which is crucial for building robust models in multi‐omics tasks (Lin et al, 2021; Yao et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The binary profile is a widely used technique for representing amino acid sequences (Qureshi et al, 2015; Yao et al, 2023). This method employs a one‐hot encoding strategy to capture both the composition and order information of a given sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to conventional machine learning methods such as random forests, this cascade architecture ensures that the deep forest algorithm can achieve profound feature exploration, thereby guaranteeing model performance. Within recent years, deep forests have also been employed on bioinformatics missions such as biological sequence analysis and multiomics data analysis. , …”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional machine learning methods such as random forests, this cascade architecture ensures that the deep forest algorithm can achieve profound feature exploration, thereby guaranteeing model performance. Within recent years, deep forests have also been employed on bioinformatics missions such as biological sequence analysis 14 and multiomics data analysis. 15,16 In this study, we proposed a novel framework for ATP identification, called ATPfinder, which enables efficient and accurate identification of ATP from collections of natural or synthetic sequences without extensive labor.…”
Section: ■ Introductionmentioning
confidence: 99%